Gene Activation Is Introduced as Cell Protection Mechanism Against Gamma Ray Irradiation: Gene Activation Against Gamma-Ray Radiation - Nikzamir, Abdolrahim; Rezaei-Tavirani, Mostafa; Razzaghi, Zahra; Rostami-Nejad, Mohammad; Hamdieh, Mostafa; Arjmand, Babak (Journal of Lasers in Medical Sciences, 2020)
Introduction: Gamma radiation is accompanied by prominent biological effects and damages. Cell proliferation and tumorigenesis are highlighted as the main resulted effects of gamma radiation on cultured cells. This study aims to assess the dysregulated mode of gene function after gamma radiation in human Jurkat cells. Methods: Six gene expression profiles from Gene Expression Omnibus (GEO) were analyzed by GEO2R to find the significant differentially expressed genes (DEGs) via gamma radiation. Action map analysis was applied to screen the query DEGs. Results: Among 108 study genes, 20 critical DEGs including AURKA, AURKB, BORA, CCNB1, CCNB2, CCNF, CDC20, CDCA8, CENPA, CENPE, CENPF, KIF18A, KIF20A, KIF23, BUB1, DLGAP5, ECT2, PLK1, SGO2, and TPX2 were introduced as down-regulated genes by the gamma-ray. Conclusion: Activators of the introduced critical genes may be the cell protector against gamma radiation.